Pengaruh Penkes pada Video Animasi terhadap Pengetahuan dan Motivasi Ibu Hamil di Rumah Sehat Bunda Athahira - Pri Hastuti; Johariyah Johariyah; Sohimah Sohimah (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Breast milk (ASI) is the best primary food for babies. Optimizing the provision of ASI is crucial in child care and in preparing the next generation. The proportion of exclusive breastfeeding is higher among mothers with good knowledge compared to those with limited knowledge. The high proportion of mothers who do not provide exclusive breastfeeding is caused by a lack of awareness of its importance, which leads to low motivation to provide exclusive breastfeeding. This study aims to determine the effect of health education using animated videos on improving the knowledge and motivation of third-trimester pregnant women to provide exclusive breastfeeding at Rumah Sehat Bunda Athahira. This study used a quantitative approach with a post-test design. The sample consisted of 15 third-trimester pregnant women selected using incidental sampling techniques. The results showed that health education using animated videos was effective in improving the knowledge and motivation of third-trimester pregnant women in providing exclusive breastfeeding. The t-test results indicated a significance value of 0.006 (p<0.05), which indicates that animated videos can improve the knowledge and motivation of pregnant women to provide exclusive breastfeeding. The use of video media was proven to be more effective in conveying information and helping respondents retain the material provided.